(untitled) (Global Journal of Human-Social Science, 2014)
GIS and Electrical resistivity method of geophysical methods has been combined for the assessment of groundwater potential in Ikeja Local Government of Lagos State, Nigeria. Ten (10) vertical electrical sounding was carried out using the High resolution Abem Terrameter Sas 4000 Earth resistivity Meter.Curve matching techniques and WinResist software were used to process and iterate VES data; AutoCAD 2012 version was used to draw the geoelectric section using the depth of each lithology and was then imported into the ArcGIS to perform several queries.